2016
DOI: 10.1186/s12859-015-0868-6
|View full text |Cite
|
Sign up to set email alerts
|

An efficient genome-wide association test for multivariate phenotypes based on the Fisher combination function

Abstract: BackgroundIn genome-wide association studies (GWAS) for complex diseases, the association between a SNP and each phenotype is usually weak. Combining multiple related phenotypic traits can increase the power of gene search and thus is a practically important area that requires methodology work. This study provides a comprehensive review of existing methods for conducting GWAS on complex diseases with multiple phenotypes including the multivariate analysis of variance (MANOVA), the principal component analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
89
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(91 citation statements)
references
References 33 publications
2
89
0
Order By: Relevance
“…For complex diseases with multivariate phenotypes, combining multiple related phenotypic 250 traits into one analysis can increase power in finding disease associations 75,76 . We combined 251 the six aforementioned quantitative trait associations into one meta-statistic using a Fisher 252 combination function modified to account for correlated traits 77 . Inter-trait correlations were 253 determined using the Pearson correlation coefficient ( Fig.…”
mentioning
confidence: 99%
“…For complex diseases with multivariate phenotypes, combining multiple related phenotypic 250 traits into one analysis can increase power in finding disease associations 75,76 . We combined 251 the six aforementioned quantitative trait associations into one meta-statistic using a Fisher 252 combination function modified to account for correlated traits 77 . Inter-trait correlations were 253 determined using the Pearson correlation coefficient ( Fig.…”
mentioning
confidence: 99%
“…Brown () and J. J. Yang () have shown that if these p values are correlated, the distribution of the T statistic approximates a gamma distribution with the shape parameter v/2 and the scale parameter 2γ under the null hypothesis. J. J. Yang, Li, Williams, and Buu () further extended the T statistic to a two‐sided test for testing pleiotropic effects. For the proposed GEE‐joint test, the T statistic follows a gamma distribution with a mean of 4 and a variance of 4+δ, where δ=cov(2 log(pmarginal),2 logtrue(pinteractiontrue)) is a function of the correlation between γ1 and β3ρ.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it can be approximated by a tenth‐order polynomial of ρ. ρ is estimated by the bias‐corrected sample correlation between γˆ1 and βˆ3 (J. J. Yang et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Methods involving the first strategy combine either the univariate test statistics (Kim, Bai, & Pan, 2015;O'Brien, 1984;Wei & Johnson, 1985) or p-values (Liang, Wang, Sha, & Zhang, 2016;van der Sluis, Posthuma, & Dolan, 2013;Yang, Li, Williams, & Buu, 2016); they are generally very easy to implement and can cope with a mixture of different types of phenotypes; however, the statistical power of those methods might heavily rely on the homogeneity of univariate test statistics (Zhu, Zhang, & Sha, 2015;Zhu, Zhang, & Sha, 2018); the most popular methods in this category include O'Brien's method (O'Brien, 1984;Wei & Johnson, 1985), trait-based association test that uses extended Simes procedure (TATES; van der Sluis et al, 2013), Fisher's combination (Yang et al, 2016), and adaptive Fisher's combination (AFC; Liang et al, 2016). The most widely used strategies for those research efforts are combining univariate analysis results, dimension reduction, and regression models.…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used strategies for those research efforts are combining univariate analysis results, dimension reduction, and regression models. Methods involving the first strategy combine either the univariate test statistics (Kim, Bai, & Pan, 2015;O'Brien, 1984;Wei & Johnson, 1985) or p-values (Liang, Wang, Sha, & Zhang, 2016;van der Sluis, Posthuma, & Dolan, 2013;Yang, Li, Williams, & Buu, 2016); they are generally very easy to implement and can cope with a mixture of different types of phenotypes; however, the statistical power of those methods might heavily rely on the homogeneity of univariate test statistics (Zhu, Zhang, & Sha, 2015;Zhu, Zhang, & Sha, 2018); the most popular methods in this category include O'Brien's method (O'Brien, 1984;Wei & Johnson, 1985), trait-based association test that uses extended Simes procedure (TATES; van der Sluis et al, 2013), Fisher's combination (Yang et al, 2016), and adaptive Fisher's combination (AFC; Liang et al, 2016). For the strategy of dimension reduction, instead of testing one phenotype at a time, one first constructs a small number of latent variables, which are linear combinations of the observed phenotypes, and then tests the associations between the latent variables and the genetic variant of interest; dimension reduction methods are, in general, suitable only when all phenotypes are normally distributed (Yang & Wang, 2012); in addition, the newly derived latent variables are usually difficult to interpret in the real-world applications; the most popular methods in this category include principal components of the phenotypes (Aschard et al, 2014), principal component of heritability (Klei, Luca, Devlin, & Roeder, 2008;Zhou et al, 2015), and canonical correlation analysis (Ferreira & Purcell, 2008;Tang & Ferreira, 2012).…”
Section: Introductionmentioning
confidence: 99%